Enhanced isobutanol production by co-production of polyhydroxybutyrate and cofactor engineering - Song, Hun Suk; Jeon, Jong Min; Bhatia, Shashi Kant; Choi, Tae Rim; Lee, Sun Mi; Park, Sol Lee; Lee, Hye Soo; Yoon, Jeong Jun; Ahn, Jungoh; Lee, Hongweon; Brigham, Christopher J.; Choi, Kwon Young; et al. (Journal of Biotechnology, 2020)
Once cells have been used to produce biochemicals, there are only a few effective ways to utilize the residual cell mass, even though the utilization of leftover cells would aid in decreasing production costs. Here, a polyhydroxybutyrate (PHB) and isobutanol co-production system was designed to address this challenge. The addition of the PHB operon into Escherichia coli conferred a metabolic advantage for alcohol production, generating 1.14-fold more isobutanol. Furthermore, following nitrogen source optimization and cofactor engineering, the engineered E. coli strain produced 2-fold more isobutanol and 0.25 g/L PHB. Moreover, E. coli cells showed higher tolerance to isobutanol with the overexpression of PHB biosynthesis genes. This co-production system resulted in an increased biomass, higher glucose utilization, and lower acetate maintenance, leading to higher productivity regarding PHB and isobutanol yield. Thus, this novel system is applicable to future fermentation studies for the co-production of PHB and isobutanol.
Keywords: Biosynthesis genes; Co-production; Cofactor engineering; Isobutanol; Nitrogen sources; Over-expression; Polyhydroxybutyrate; Production cost; Acetates; Butanols; Escherichia coli; Fermentation; Glucose; Hydroxybutyrates; Metabolic Engineering; Polyhydroxyalkanoates; Acetate; Co-production; Escherichia coli; Glucose utilization; Isobutanol; Polyhydroxybutyrate